Investigation of radionuclide concentration in technological wastes of South-Ukrainian NPP - M. D. Bondarkov; A. M. Maksimenko; I. M. Vyshnevsky; V. A. Zheltonozhsky; M. V. Zheltonozhska; L. V. Sadovnikov; S. V. Ilichyov; V. V. Boyarischev; V. Muller (Ядерна фізика та енергетика)
Investigation of radionuclide concentration in liquid and solid technological wastes of South Ukrainian NPP was carried out. The coordinated change of radionuclides in all samples is indicated. Simple correlation for evaluation of radionuclide concentration from data of 60Co and 137Cs activity was obtained.